Status of Long Term Care Needs of Aged People in Elders’ Homes in Sri Lanka - Kaluthantiri Weeratunga, Manori (My University, 2020)
Migration is an important component in terms of understanding population change of a geographical area. Internal migration has been identified as a vital force in development with its characteristic of transfer of knowledge and skills through the point of destination to origin and vice versa. The main objective of the study is to identify the migration flows as well as to recognize the inter-district efficiencies of migration in Sri Lanka, which has not been examined before. Although migration flows have been identified with percentage of migrants flows in the General Report of the 2012 Population Census, inter-district of migration efficiencies have not been examined demographically with use the formula use to calculate inter-region migration efficiencies. of A meaningful way to understand mobility between regions is to calculate efficiency of migrations between a given region and the rest of the country which has been effectively and with the use of proper demographic techniques have been presented in this study. The results of the study reveal that the spatial orientation of migration (in the present study the spatial orientation is district as the unit of analysis) is towards Western Province of the country where capital city of Sri Lanka as well as Industrial zone is located. However, Vavunia, which is a waraffected district has gained inward mobility because of return migrants after the conclusion of the war in 2009. Although migration efficiency of Jaffna district is relatively high, the flow is outward by losing about 60 out of 100 people to the rest of the country. The importance lies in the recognition of spatial dynamics ( how migration behaves over defined physical space(s)) in the implementation of social and infrastructure policies as well as the labour market policies.
Keywords: Internal migration, Spatial orientation, Efficiencies of migration